INOVASI OLAHAN PRODUK KERIPIK PISANG VARIAN RASA DESA MEKARSARI KECAMATAN NARMADA KABUPATEN LOMBOK BARAT - Fadli, M Rizal; Fitriani, Baiq Yati; Nispiani, Nurlaela; Aci, Intan Pandini; Rahmawati, Putri; Noviyanti, Adelia; Sulastri, Iras; Chayati, Indry; Nisah, Raodatul; Hartita, Yuyun (Jurnal Wicara, 2023)
This service focuses on the development of one of the Natural Resources (SDA) communities in Mekarsari Village, Narmada District, namely the banana chip business which is considered to have not maximized its utilization and development. The Mekarsari community's banana chip business has not yet developed because the marketing and taste variations of the business are less varied so that consumer appeal is very minimal. Therefore, this community service seeks to develop the banana chip business by conducting community service based on the Asset Based Community Development (ABCD) approach. ABCD is an approach to community service by seeing and knowing the strengths and weaknesses of existing businesses in an area to create an empowered and thriving community. This service begins with observing the location first to find out the data and what businesses need to be developed by conducting interviews with the Mekarsari village community. The results of this service show that the new flavor variations such as chocolate, vanilla and oreo have a higher selling value than the previous banana chip flavor variations. This study recommends that future researchers carry out further dedication to the development of banana chip business marketing.